AVATAR ME, 2020: Co-produced with Teater Nordkraft - Winkelhorn, Kathrine (Peripeti, 2023)
The festival is produced by Wildtopia and presented in collaboration with theatre partners, Teater Nordkraft in Aalborg and Teater Viirus in Helsinki. Cast: Marcela Nistor, Robin Khor Yong Kuan, Bertwin Ravi D’souza, Lalisa Costa and Lillian Tshabalala. Director: Tue Biering. Producer: Annette Max Hansen. Dramaturg and co-director: Linn Haldrup Lorenzen. Coordinator and co-director: Camilla Gürtler.